Placenta Previa Oclusiva Parcial diagnóstico y tratamiento en multípara - Sabando Macías, Eliana Katherine (2020)
This clinical case study aims to substantiate the importance of timely diagnosis and treatment in pregnant women with placenta previa to reduce maternal-fetal complications. Clinical case: 34-year-old female patient, with a history of multiparity, an abortion 9 years ago, a previous cesarean section 8 years ago, and insufficient pregnancy controls. The patient presents with a clinical picture of approximately 3 hours of evolution, presenting a moderate amount of bright red transvaginal bleeding without other accompanying symptoms. On physical examination, single living fetus globular abdomen, present fetal movements perceptible by the mother, sporadic uterine activity. Multiparous genitalia at speculoscopy showed bright red active bleeding without clots of moderate quantity, a slightly open cervix. Laboratory tests and obstetric ultrasound are requested where she reports: 33 weeks pregnancy; partial occlusive placenta previa. Admission is decided to assess the maternal-fetal binomial. The indicated treatment: absolute rest, hydration, lung maturation, tocolysis, analgesic. It was a preterm pregnancy with expectant management, due to the new episode of bleeding that the patient presented on the eighth day of being hospitalized, it was decided to terminate the pregnancy by discharge (cesarean section). A female APGAR 7-8 weight newborn was obtained with a pre-term diagnosis plus respiratory distress reported by neonatology. Post-caesarean section blood count of the user indicates moderate anemia is managed with parenteral iron. Later the discharge is granted.